Forest Wealth of India - Sarkar, K. K. (Indian Forester, 1937)
Indla is a vast country having an area of about 1,099,313 square miles, of which nearly 261,219 square miles are under forests, giving an outturn of 1,201 c. ft. of timber and fuel and Rs. 42 of minor products per square mile in 1932-33. Much has been of late done by research and active propaganda to find use and market for this huge quantity and to make it stand foreign competition. Thus the import trade is declining markedly year by year. But few individuals can possibly afford to invest in forests a form of capital which requires long and patient waiting, careful and well-chalked-out working plans and strict adherence to same, a dragon-like watchfulness against forest fires, indiscreet or over-cutting of the immature standing crops and the commission of forest offences, and, as they are so intimately bound to our best interests, viz., national prosperity and safety, they may, with advantage, remain under the management of the Central Government.